ANALISIS KEGAGALAN SUPLAI DIRECT CURRENT BATTERY CHARGING POWER SUPPLY GLIDE PATH MEREK SELEX TYPE 2110 - Rinoto, Imanuel Kiyan Pranata; Toni; Roza, Febria (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
The abstract contains a brief Aircraft navigation is a series of activities carried out by the pilot and/or navigator to determine the geographical position of the aircraft. Glide Path is a transmitter that provides distance angle guidance signals or helps the aircraft to land exactly at the landing point. Battery Charging Power Supply is one of the modules in GP equipment which functions as a low voltage DC provider, namely at +5V, +12V, and -12V, and also as a 24 Volt backup battery charger module when receiving AC input. In this research, there were indications of problems with the BCPS Glide Path module. This research aims to analyze the factors that cause equipment problems and enable actions that can be taken to return the backup battery function to normal conditions. The research method applied is a qualitative approach. This method is used to identify factors that trigger problems with Glide Path equipment. The problem that occurred with the Battery Charging Power Supply 1 (one) module which could not work in On Battery mode (supplying a DC source from the backup battery to the equipment) was found to be damage to the IC 74HC02 (U13) and IC 74HC14 (U15) components. The decision taken as an effort to resolve the problem was to take systematic action to replace components on the BCPS that were damaged (short circuit), namely (U13 and U15) with new ones.